Seismic monitoring of CO2 injection into a depleted gas reservoir – Otway Basin Pilot Project, Australia - Urosevic, Milovan; Pevzner, Roman; Shulakova, V.; Kepic, Anton; Caspari, Eva; Sharma, S. (Elsevier, 2011)
The use of depleted gas fields for CO2 storage as well as CO2-based enhanced gas recovery are of global importance. Thus, the CO2CRC Otway Basin Pilot Project provides important experience in establishing whether such scenarios can be monitored by geophysical techniques, in particular seismic time-lapse methodology. Injection of CO2 into a depleted gas reservoir (with residual gas in the Otway case) does not present favourable conditions for the application of geophysical monitoring techniques. Simulation of the CO2 injection process at Otway shows that changes in elasticity of the reservoir rock will be quite small and difficult to monitor even with the most powerful time-lapse (TL) seismic methodologies. Consequently, the design and implementation of the monitoring program had to address these issues. To increase the sensitivity of TL seismic we combined 3D VSP with 3D surface seismic. For land seismic case, we achieved excellent repeatability with 3D time lapse surveys, which at the reservoir level produced normalised RMS difference values of about 20% for surface seismic and 10% for 3D VSP, respectively. Still due to very small time lapse signal, the primary use of 3D surface seismic was for assurance monitoring. Borehole seismic measurements confirmed that time-lapse is too small to be reliably estimated and analysed from repeated seismic measurements. Finally, post-injection reservoir simulation and accompanying seismic modelling suggest that a prolonged CO2/CH4 injection should produce only negligible change of the elastic properties of the Naylor reservoir.